AN INVESTIGATION OF INFORMATION SEEKING BEHAVIOUR OF COMPUTER SCIENCE AND INFORMATION TECHNOLOGY UNDERGRADUATES: A QUALITATIVE APPROACH - Mohd Saad, Mohd Sharif; A.N., Zainab (Malaysian Journal of Library and Information Science, 2009)
It is a common fallacy to assume that undergraduates are skilled in finding and evaluating resources for their various learning needs. Information professionals need to find out strategies and courses of action undertaken by undergraduate students in order to perhaps improve information literacy skills or user education programmes. This qualitative study uses the diary, emails interaction and in depth face to face interview approach involving 14 final year Computer Science and Information Technology undergraduates whom shared their information search and use process. The objectives of this study are to find out the followings: (a) the decision on deciding research topics by final year students; (b) the sources and channels of information they use and prefer; (c) the utility of libraries and librarians; (d) the use of the Internet; (e) the search strategies adopted; (f) their thoughts on intellectual property and ethical issues. Among the main information sources used were the Internet, books and previous final year project reports. They also seem to rely a lot on their friends and lecturers as their source o information. Very few used journal articles, seminar papers or other sources. An understanding of their information seeking behaviour patterns is the focus of this paper. Informants’ thoughts and feeling on the library services and the ethical use of information will be shared.